Associations between the gut microbiome and fatigue in cancer patients - Joud Hajjar; Tito Mendoza; Liangliang Zhang; Siqing Fu; Sarina A. Piha-Paul; David S. Hong; Filip Janku; Daniel D. Karp; Alexej Ballhausen; Jing Gong; Abdulrazzak Zarifa; Christine B. Peterson; et al. (Scientific Reports, 2021)
Abstract Fatigue is the most prevalent symptom of cancer and its treatments. Changes in the intestinal microbiome have been identified in chronic fatigue syndrome and other neuropsychiatric disorders, and cancer patients. However, the association between intestinal microbiome and fatigue in patients with advanced cancers has not been evaluated. Understanding the connection between intestinal microbiome and fatigue will provide interventional and therapeutic opportunities to manipulate the microbiome to improve fatigue and other patients’ reported outcomes. In this project, we aimed to identify associations between microbiome composition and fatigue in advanced cancer patients. In this cross-sectional observational study at a tertiary cancer care center, we included 88 patients with advanced, metastatic, unresectable cancers who were in a washout period from chemotherapy. We measured fatigue using the MD Anderson Symptom Inventory—Immunotherapy fatigue score, and used 16srRNA to analyze intestinal microbiome. Using correlation analysis we found that Eubacterium hallii was negatively associated with fatigue severity scores (r = − 0.30, p = 0.005), whereas Cosenzaea was positively associated with fatigue scores (r = 0.33, p = 0.0002). We identified microbial species that exhibit distinct composition between high-fatigued and low-fatigued cancer patients. Further studies are warranted to investigate whether modulating the microbiome reduces cancer patients’ fatigue severity and improves their quality of life.